2009
DOI: 10.1002/dc.21209
|View full text |Cite
|
Sign up to set email alerts
|

Women ≥30 years of age with low grade squamous intraepithelial lesion (LSIL) have low positivity rates when cotested for high‐risk human papillomavirus: Should we reconsider HPV triage for LSIL in older women?

Abstract: High-risk human papillomavirus (HR-HPV) testing for colposcopy triage of low grade squamous intraepithelial lesion (LSIL) is not recommended because of high positive rates in young women. It remains unclear whether HR-HPV testing may be useful for triage of older women. We compiled HR-HPV data for women aged >or=30 years with LSIL for the period March 1, 2006 to February 28, 2008. Follow-up cervical biopsy information was collected for the period March 1, 2006 to August 15, 2008. We used the Hybrid Capture II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
2
15
1
Order By: Relevance
“…Based on previous studies, high-risk HPV was detected in 83% of women with LSIL cytology and a mean age of 24.9 years. Our result is in agreement with other studies which implies that it might be useful to triage women in the 21-40 year age group with LSIL (Ronco et al, 2007;Thrall et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Based on previous studies, high-risk HPV was detected in 83% of women with LSIL cytology and a mean age of 24.9 years. Our result is in agreement with other studies which implies that it might be useful to triage women in the 21-40 year age group with LSIL (Ronco et al, 2007;Thrall et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Our data and other published studies have shown that the prevalence of both hrHPV DNA positivity and CIN 2/3 decline with age in women with LSIL Paps [5,7,26,30]. Another study demonstrated that older women are more likely to have persistent HPV infection than younger women, even though most infections by the hrHPV types still clear in 2 years [31].…”
Section: Discussionmentioning
confidence: 52%
“…Since only a minority of patients with LSIL are found to harbor or later develop a high-grade CIN [21,22 ]or even more rarely a cervical carcinoma [22,23], management of LSIL remains a major challenge to system efficiency [25]. With ongoing accumulation of age-stratified data sets, the utility of HPV testing in older patients with LSIL Paps continues to spark interest [5,6,7,26]. To the best of our knowledge, our study is the largest to date to examine histopathological follow-up of patients from diverse older age groups with LSIL cytological interpretations and concurrent hrHPV DNA testing.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also suggested that HR HPV testing of older women with LSIL may be rational because of the relatively high percentage of women who were negative for HR HPV. 3,7,13 Given the ACOG guidelines for HR HPV cotesting in women aged 30 years, in many cases HR HPV status may already be known. In this scenario, a known prior positive HR HPV cotesting result would avoid the need for and the additional cost of reflex HR HPV testing of a woman with LSIL cytology.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have suggested that HR HPV DNA testing may be useful in triaging older women with LSIL. [2][3][4] With the introduction of HR HPV cotesting, more and more women with LSIL have been tested for HR HPV. The objective of the current study was to correlate the status of HR HPV and the subsequent detection of high-grade dysplasia in women with LSIL.…”
mentioning
confidence: 99%